(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the analysis of the foundations of spiritual stability in Uzbekistan. It reveals that the country’s independence, especially the reforms carried out in subsequent years, created real conditions for the development of forms of social consciousness, the acquisition of a humane character by the social psyche and ideology, and the optimization of the process of spiritual production. The article describes the content and essence of these factors.